(untitled) (Brazilian Journal of Radiation Sciences, 2021)
Hydrogels are cross-linked polymer networks, which are of interest in biomedical applications such as drug delivery system. To achieve successful results in this kind of application it is essential to understand the diffusion mechanisms which are generated in the hydrogel during the swelling process. For this reason, this work consists in carrying out an analysis of the swelling kinetics in hydrogels elaborated through gamma radiation and the combination of gamma radiation with thermal cycling processes. The hydrogels were synthesized using biocompatible polymers irradiating their solution at different doses. A swelling test was performed and the diffusion coefficient and the diffusional exponent were calculated, making an analysis of the kind of diffusion mechanism in the hydrogel matrix. This test showed that the higher radiation absorbed used to get the gels, the lower the swelling percentage, as well as the diffusion coefficient of the water molecules in the hydrogel. The results of the kinetic analysis showed an anomalous diffusion mechanism for the gels obtained at 25 kGy. For those gels of 30 kGy, the diffusion was Fickian. Finally since those gels of 35 kGy was not possible to classify it according to the Fick’s law of diffusion. Furthermore, we could observe that the hydrogels that had been obtained by thermal cycling and by irradiation had higher swelling percentages compared to those that were only cross-linked by irradiation. This analysis allowed us to understand the intrinsic behavior of the polymer / solvent mesh system at different doses and under two different crosslinking conditions.